2007
DOI: 10.2174/156720107782151214
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Muco-Adhesive Formulations for the Treatment of Infectious Periodontal Diseases

Abstract: Extensive efforts have recently been focused on targeting a drug or delivery system in a particular region of the body for extended period of time, not only for local targeting of drugs but also for the better control of systemic drug delivery. The concept of periodontal drug delivery systems has fascinated many investigators to the possible use of various polymers, which can overcome various physiological barriers in long-term drug delivery, there by rendering the treatment more effective and safe for local d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 118 publications
0
4
0
5
Order By: Relevance
“…11 Thus, an important goal in the development of drug delivery systems is to maximize adhesiveness. 12 Ten-percent DOX gel has been used in the treatment of periodontitis and has been proven to more effectively reduce the periodontal probing depth (PPD) and improve the clinical attachment level (CAL) compared with SRP alone, thereby improving the quality of life of individuals with periodontitis. 13,14,15 However, Garrett et al 16 reported that the treatment of moderate to severe periodontitis with 10% DOX was only as effective as SRP.…”
Section: Introductionmentioning
confidence: 99%
“…11 Thus, an important goal in the development of drug delivery systems is to maximize adhesiveness. 12 Ten-percent DOX gel has been used in the treatment of periodontitis and has been proven to more effectively reduce the periodontal probing depth (PPD) and improve the clinical attachment level (CAL) compared with SRP alone, thereby improving the quality of life of individuals with periodontitis. 13,14,15 However, Garrett et al 16 reported that the treatment of moderate to severe periodontitis with 10% DOX was only as effective as SRP.…”
Section: Introductionmentioning
confidence: 99%
“…Однако такие методики местного применения противомикробных препаратов, как субгингивальное орошение, обеспечивают локальную доставку препарата, но не обеспечивают его контролируемое или замедленное высвобождение, что, безусловно, отражается на эффективности использования препарата. Так, системы с замедленным или контролируемым высвобождением представляют собой биосовместимую матрицу, содержащую одно или несколько действующих лекарственных веществ, использующихся для этиотропной (противомикробные препараты), патогенетической (стероидные и нестероидные противовоспалительные препараты) и симптоматической терапии (анестезирующие препараты) [9,11,24] [22,28]. В зависимости от состава матрицы систем доставки препарата с пролонгированным или контролируемым высвобождением классифицируют на биорезорбируемые и нерезорбируемые.…”
Section: Clinical Medicineunclassified
“…В зависимости от состава матрицы систем доставки препарата с пролонгированным или контролируемым высвобождением классифицируют на биорезорбируемые и нерезорбируемые. В первом случае нет необходимости извле кать препарат из пародонтального кармана по истечении срока действия, в то время как нерезорбируемые системы требуют повторного визита к стоматологу с целью удаления матрицы, что повышает вероятность повреждения тканей в процессе извлечения [12,22,28].…”
Section: Clinical Medicineunclassified
See 2 more Smart Citations